Harnessing the Power of Machine Learning and Artificial Intelligence in Seed Science and Technology: A Review - AV BARAD; JB PATEL; YASH J CHAUDHARY; JYOTI SONDARVA (Seed Research, 2024)
Integrating machine learning (ML) and artificial intelligence (AI) into seed science and technology represents a transformative paradigm in agricultural research. This study explores the potential and applications of ML and AI methodologies to enhance various facets of seed-related processes. From seed viability assessment to crop yield prediction, using advanced algorithms enable a more precise and efficient understanding of seed characteristics. The abstract delves into specific applications such as predictive modeling, image recognition, and data-driven decision-making in seed breeding. By harnessing the power of ML and AI, researchers and practitioners in seed science can revolutionize traditional approaches, fostering sustainable agriculture and ensuring food security in an ever-evolving global landscape.